SEMANTIC DIFFERENTIATION OF THE UNITS “FEAR,” “ANXIETY,” AND “TERROR” IN ENGLISH (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article analyzes the semantic differentiation of the English units fear, anxiety, and terror. It highlights the semantic scope of these lexical units, their stylistic features, their emotional-expressive coloring, and the differences in their use in speech. The study employs explanatory dictionaries, semantic analysis, contextual analysis, and comparative methods. As a result, the common and distinctive semes of fear, anxiety, and terror are identified, and their role in expressing emotional states in English is clarified. The findings of the research are of considerable importance for semasiology and linguosemantics.